Search for pair-produced resonances decaying to jet pairs in proton-proton collisions at √s=8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; Hartl, C.; Hoemann, N.; et al. (ELSEVIER, 2015)
Results are reported of a general search for pair production of heavy resonances decaying to pairs of hadronic jets in events with at least four jets. The study is based on up to 19.4 fb(-1) of integrated luminosity from proton-proton collisions at a center-of-mass energy of 8 TeV, recorded with the CMS detector at the LHC. Limits are determined on the production of scalar top quarks (top squarks) in the framework of R-parity violating supersymmetry and on the production of color-octet vector bosons (colorons). First limits at the LHC are placed on top squark production for two scenarios. The first assumes decay to a bottom quark and a light-flavor quark and is excluded for masses between 200 and 385 GeV, and the second assumes decay to a pair of light-flavor quarks and is excluded for masses between 200 and 350 GeV at 95% confidence level. Previous limits on colorons decaying to light-flavor quarks are extended to exclude masses from 200 to 835 GeV. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V. This is an open access article under the CC BY license.
Keywords: CMS; Physics; Dijets; CHIRAL COLOR; SUPERSYMMETRY; SQUARK; Astronomy & Astrophysics